A Study on the Technology Content Assessment Based on Aspects of Food Safety in the Food Ingredient Company - Aji, Permadi Bayu; Wahyuni, Hana Catur (Spektrum Industri, 2022)
Technological complexity assessment is one of ways to implement the continuous improvement process. This company is a food ingredient company that assure that their products do indeed meet customer requirements of food safety and quality. This study aims to assess the level of technological sophistication based on food safety aspects using technometric and AHP integration. Technological assessment is carried out on the production process of pregelatinized starch as premium and specialty product and its supporting processes within the company. The technometric approach will assess the level of sophistication of each technology component (technoware, humanware, infoware, and orgaware). And AHP is used to determine the contribution of each technology component. After that, computation of the technology contribution coefficient is done to determine the company’s technology level. The results showed that the highest to lowest value of the contribution of sophistication of each component of technology is orgaware with a sophistication value of 1.064, then infoware with a value of 1.047, followed by humanware 0.868, and lastly is the technoware component which is 0.692. The TCC value of the company is 0.909 which indicates that the company has a highly sophisticated technological with modern technology levels.